1990
DOI: 10.1063/1.344583
|View full text |Cite
|
Sign up to set email alerts
|

Particle interaction in numerical micromagnetic modeling

Abstract: Numerical micromagnetic modeling of a single particle and small numbers of particles has recently greatly increased our understanding of fine particle magnetizing processes, but the behavior of a large number of such interacting particles is not yet completely understood. The analysis presented here shows that the moving-model Preisach approach, as a framework for explaining the behavior of such a distribution, is plausible; however, the proportionality factor is considerably different from the one that had be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Then, each value of m on the normalized m À H A plane represents the measured coercive field, H c , of all the particles having an intrinsic coercive field, H cðiÞ , which is shifted along the field axis by a quantity equal to the dipolar interaction field for that specific value of m. This allows to rewrite Eq. (2) by interpreting the applied field H A as the measured coercive field H c and the total field, H tot as the intrinsic coercivity, [47][48][49] H cðiÞ ¼ H c À am:…”
Section: General Considerationsmentioning
confidence: 99%
“…Then, each value of m on the normalized m À H A plane represents the measured coercive field, H c , of all the particles having an intrinsic coercive field, H cðiÞ , which is shifted along the field axis by a quantity equal to the dipolar interaction field for that specific value of m. This allows to rewrite Eq. (2) by interpreting the applied field H A as the measured coercive field H c and the total field, H tot as the intrinsic coercivity, [47][48][49] H cðiÞ ¼ H c À am:…”
Section: General Considerationsmentioning
confidence: 99%
“…Numerical micromagnetic Manuscript received Feb. 15, 1995. studies [5] have shown that, for particles used in recording media, the field required to nucleate a reversal, H N , is also much larger than that required to propagate the reversal throughout the particle.…”
Section: Dynamics Of Hysteronsmentioning
confidence: 99%
“…0 is the coercivity without interactions [11,12]. It was shown that in the calculations the interactions with the surrounding particles can be truncated at the 3rd coordination shell.…”
Section: Interaction Field Distributionmentioning
confidence: 99%